Impact Of Industrial Area Development on National and Regional Economies In Indonesia: Case Study And Policy Implications Post-Pandemic - Suyanto; Alisyah, La Ode; Jusnita, R. Ayu Erni; Baruno, Agustiawan Djoko; Amalia, Yustisia Amalia (Journal of International Multidisciplinary Research, 2024)
This study examines the complex consequences of industrial area development on both the national and regional economies of Indonesia, with a specific focus on the interaction between these two domains. This research employs a comprehensive case study methodology to examine the policies crucial for ensuring sustainable economic growth in the aftermath of the pandemic. Industrial expansion's direct and indirect effects on job creation, economic diversification, technological advancement, and resource distribution are all examined in this analysis. Considering the varying degrees of development and infrastructure across Indonesia's regions, the study also identifies the distinct impacts of economic disparities across these areas. The results emphasize the need for tailored policy interventions that consider regional discrepancies and foster fair economic growth post-pandemic. Contributing to the economic recovery of the nation, the study finds sectors of the Indonesian economy with potential for expansion in the post-pandemic period. Employing the shift-share analysis and qualitative descriptive method, help determine if any changes have occurred in the configuration of the economic system during the post-pandemic period. The findings indicate that each of the five provinces, namely Bali, Riau Islands, Banten, East Borneo, and Yogyakarta, possesses distinct competitive advantages that are unique to their respective regions. However, none of the industries in these five areas possesses a significant degree of expertise in any particular industry. The research also emphasizes the lack of dedicated business activities focused on a specific industry.